Redefinition of Nafkah in the Pattern of Child Protection and the Formation of Family Problems in Indonesia - M Nur Syafiuddin; Rachmad Safa’at; Prija Djatmika; Istislam Istislam (International Journal of Nusantara Islam, 2021)
As the most beautiful gift as well as the mandate of Allah SWT. as well as considering the child's position in family, community and state life, children must get the best protection in their development process, including through granting children's rights to a living. Several laws and regulations in Indonesia define a living as meeting the material needs of children. Such a definition raises various problems in the pattern of child protection and the formation of the benefit of families in Indonesia. This study aims to describe the redefinition of livelihoods in child protection efforts and the formation of the benefit of families in Indonesia. This research method uses normative legal research with a philosophical and statutory approach and uses a prescriptive analytic method. The results show that in the pattern of child protection and the formation of family welfare in Indonesia, children's livelihoods must be defined as meeting children's material needs so that children can survive and as fulfilling children's immaterial needs so that children can improve their quality of life.